Treatment of Pulp and Paper Industry Wastewater by using Fenton Method - Salsabilla A Yani; Tuty Emilia Agustina; M. Fitri Hadiah (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2020)
The pulp and paper industry wastewater has not met the environmental uality standards set by the government so it may causes pollution to the environment; therefore, it is necessary to find a better wastewater treatment. The problem of this study is how to find the wastewater treatment alternative in order to get a more effective and efficient treatment. Fenton reagents are H2O2 compounds (hydrogen peroxide) with iron catalysts and is one of the Advance Oxidations Process (AOPs) methods, which can be used as an alternative to process wastewater from the pulp and paper industry. In this study, the ratio of Fenton reagent molar concentration, temperature, and stirring time were varied, with stirring speed of 300 rpm, Fenton reagent volume of 25 mL, and pH set at 3. The visible parameters in this study were COD and TSS degradation. From this study, the best ratio of Fenton reagent is 1:2000, where this ratio can reduce the COD from 1002 mg/L to 176.05 mg/L and the TSS from 125 mg/L to 49.3 mg/L. This value has met the environmental quality standards for the pulp and paper industry set by the Indonesian government.